REALIZING CHARACTER EDUCATION TOWARDS A HUMANISTIC EDUCATION - Uswatun Chasanah (TAWASUT, 2013)
In order to realize the character education towards a humanistic education, it is definitely required an implementation of character education in the learning process, whether in school or out of school. The concept of character education should be reflected in its planning, implementation, and evaluation. The planning of character education is carried out by preparing a character-based syllabus and learning implementation plan (RPP) by integrating character values which is in-line with the indicators into that syllabus and implementation learning plan. While implementation of character education is executed through personal development activities, integrating of character values in all subjects, developing the school culture which is based on character-oriented and on valuable learning. The evaluation of character education should be emphasized and be focused on affective aspects of the students, namely the assessment towards their behavior or actions, neither on their understanding, knowledge, nor on their spoken words.Keywords:  character education, humanistic education, akhlāq, value, moral